Aflatoxin B1 disrupts blood-testis barrier integrity by reducing junction protein and promoting apoptosis in mice testes. (February 2021) - Huang, Wanyue; Liu, Menglin; Xiao, Bonan; Zhang, Jian; Song, Miao; Li, Yanfei; Cao, Zheng
Abstract: Aflatoxin B1 (AFB1 ) is an unavoidable food and environmental contaminant, which can lead to disorders in spermatogenesis and its mechanism remains unclear. The blood-testis barrier (BTB) is responsible for ensuring normal spermatogenesis in testes. Therefore, we hypothesized that disruption of the BTB was involved in AFB1 -induced spermatogenesis disorders. To confirm our hypothesis, male Kunming mice were orally gavaged AFB1 (0, 0.375, 0.75, or 1.5 mg/kg) for 30 days. Primarily, we first proved that AFB1 disrupted the BTB integrity. Then, AFB1 decreased BTB-related junction protein expression and elevated Sertoli cell apoptosis, which were associated with oxidative stress. Additionally, AFB1 upregulated the p-p38 MAPK/p38 MAPK ratio. These results collectively indicated that AFB1 disrupted the BTB via reducing the expression of BTB-related junction protein and promoting apoptosis in mice testes, which were associated with the oxidative stress-mediated p38 MAPK signaling pathway. Graphical abstract: AFB1 has testicular toxicity, and eventually leads to spermatogenesis disorder. The BTB is a physical barrier in testes for maintaining spermatogenesis. Our study manifested that AFB1 disrupted BTB via reducing BTB-related junction proteins expression and promoting cell apoptosis in mice testes, which were associated with oxidative stress-mediated p38 MAPK signaling pathway, and providing a novel mechanism of reproductive toxicity induced by AFB1 . Image 1 Highlights: Aflatoxin B1 disrupts blood-testis barrier (BTB) integrity in mice testes. Aflatoxin B1 disrupts BTB by reducing BTB-related junction protein expression. Aflatoxin B1 disrupts BTB by promoting apoptosis. Aflatoxin B1 disrupts BTB are associated with the p38 MAPK signaling pathway.